SELFISHNESS IN JAMES CAMERON S AVATAR CHARACTER ANALYSIS - Runtu, Mia Celsia; Mogea, Tini; Lolowang, Imelda (Journal of English Culture, Language, Literature and Education, 2022)
The purpose of this study is to reveal the selfishness of Colonel Miles Quaritch which is one of the main characters in the movie Avatar< em> by James Cameron and also to analyze what the causes and effects of the selfishness are In conducting this research the researcher uses qualitative research in which the data collected in the form of words and presented in descriptive form so the data that the researcher gets is only from the movie script and other books that relation to this research In this research the movie script was analyzed with objective approach it means that the data are found from intrinsic point of the movie script Avatar< em> From the result shows that selfishness is a bad trait to have in a person s attitude The researcher calls it s a bad trait because it does not only bring no benefit to the person himself but also to another person surrounds him Collonel Miles Quaritch is a selfish person It can be seen from his actions that ignoring the opinions of others and neglecting the safety of the troop to achieve his goal The Causes of the selfishness of Colonel Miles are ambition arrogance and madness And the effects of selfishness of Colonel Miles are losing the war and Colonel Miles killed by Neytiri < p>